Neonatal Alloimmune Thrombocytopenia: Antenatal and Postnatal Imaging Findings in the Pediatric Brain - Dale, Sonia T. (AJNR Am J Neuroradiol, 2002)
BACKGROUND AND PURPOSE: Neonatal alloimmune thrombocytopenia (NAIT) is a maternal-fetal platelet antigen incompatibility disorder estimated to occur in one of 2000 to 5000 neonates. The diagnosis is made serologically by showing parental platelet antigen incompatibility and the presence of maternal platelet antibodies. In the absence of formalized antenatal screening, the radiologist has an important role to play in the recognition of this disorder, which has significant implications for the index case and any subsequent offspring. Our aim was to characterize the neuroradiologic findings and identify, if possible, a consistent pattern of neurologic injury typical of NAIT. METHODS: We retrospectively reviewed the ultrasonograms, CT scans, MR images, and medical histories of six patients (21 weeks gestation to 9 years old) with intracranial injury secondary to serologically proved NAIT. RESULTS: Hemispheric porencephalic cysts (n = 6), primarily located within a temporal lobe with extension into other lobes, were seen on the ultrasonograms, CT scans, and MR images of all six children. In five cases, this was thought to represent encephaloclastic porencephaly and, in one case, schizencephaly (agenetic porencephaly). Six children had ventriculomegaly of varying degrees and severity and asymmetry. Extra-axial hemorrhages (n = 2), intraventricular hemorrhage (n = 1), acute parenchymal hemorrhage (n = 2), and neuronal migrational disorder (n = 1) occurred with varying frequency. CONCLUSION: Antenatal or early postnatal neuroradiologic imaging showing hemispheric porencephaly and lateral ventriculomegaly is a recognizable pattern of cerebral injury suggestive of the diagnosis of NAIT. In the absence of a cost-effective screening program of primiparous women and neonates for this disease, the radiologist has an important role to play in the recognition of this disease entity. It is crucial for the reporting radiologist to consider the possibility of NAIT in any child with antenatal hemorrhage and, more importantly, with the pattern of cerebral injury described above. Because a high percentage of subsequent pregnancies might be equally or more severely affected, antenatal management directed at preventing intracranial hemorrhages in utero has become of significant clinical importance.